Conformity to the Opinions of Other People Lasts for No More Than 3 Days. (July 2014) - Huang, Yi; Kendrick, Keith M.; Yu, Rongjun
When people are faced with opinions different from their own, they often revise their own opinions to match those held by other people. This is known as the social-conformity effect. Although the immediate impact of social influence on people's decision making is well established, it is unclear whether this reflects a transient capitulation to public opinion or a more enduring change in privately held views. In an experiment using a facial-attractiveness rating task, we asked participants to rate each face; after providing their rating, they were informed of the rating given by a peer group. They then rerated the same faces after 1, 3, or 7 days or 3 months. Results show that individuals' initial judgments are altered by the differing opinions of other people for no more than 3 days. Our findings suggest that because the social-conformity effect lasts several days, it reflects a short-term change in privately held views rather than a transient public compliance.